Should arboviruses be the only diagnosis hypothesis in pregnant women in endemic areas presenting with a rash? - Quintans,Maria Dolores Salgado (2019)
Abstract Listeria is an unusual pathogen that causes neonatal infection with high morbidity and mortality. We present the case of a premature newborn whose mother had a rash during pregnancy; the newborn had severe early sepsis because of Listeria monocytogenes and histopathologically suggestive findings of the placenta. Obstetricians and neonatologists should suspect listeriosis in cases with compatible epidemiological history, clinical features, and examination findings of the placenta.